Analysis on GPS-RTK techniques for continuous stuctural monitoring - Asyran, Muhammad; Setan, Halim; Mat Amin, Zulkarnaini (2004)
GPS Real Time Kinematics (RTK) can be categorized as one of the new positioning techniques in Malaysia. Unlike the conventional geodetic measurements, RTK has made the task of continuous structural monitoring becomes quicker and effective, without sacrificing much in terms of accuracy and reliability. Continuous structural monitoring is important for safety assessment. This paper discusses the potential of using GPS RTK for continuous structural monitoring in Malaysia. For that purposes, GPS data was observed (at Penang Bridge) using Leica 500 GPS receiver at the rate of 1 Hz. The post processing strategy employs Fourier and Wavelet analysis, together with MATLABÂ® software, to analyze the bridge vibration and the movement trends. The results indicate the practicality of using GPS RTK for continuous structural monitoring.